Prevalence of Hepatitis A virus (HAV) and Hepatitis E virus (HEV) in patients presenting with acute viral hepatitis: A 3-year retrospective study at a tertiary care Hospital in Western India - Meghna S Palewar; Suvarna Joshi; Geetanjali Choudhary; Rashmita Das; Ashish Sadafale; Rajesh Karyakarte (Journal of Family Medicine and Primary Care, 2022)
Context: Viral hepatitis caused 1.34 million deaths in 2015, a number comparable to the deaths caused by tuberculosis and higher than that caused by human immunodeficiency virus (HIV). Hepatitis A virus (HAV) and hepatitis E virus (HEV) are important causes of acute viral hepatitis (AVH) and acute liver failure (ALF). Due to the paucity of data, the exact burden of the disease in western India is not established. Objective: Considering this background, the present study aims to determine the prevalence, epidemiology, and biochemical correlation in AVH due to HAV and HEV. Setting and Design: It was a retrospective observational study conducted over 3 years from January 2018 to December 2020 in a tertiary care hospital of Western India. Material and Methods: The study population included 1,807 patients (outdoor and hospitalized) having clinical features of AVH. All serum samples from these patients were tested in duplicate for immunoglobulin M (IgM) anti-HAV and IgM anti-HEV antibodies using commercially available enzyme-linked immunosorbent assay (ELISA) kits. The liver function tests (LFTs) were also monitored. Results: Of the 1,807 specimens processed from the patients with AVH, 120 (6.70%) were positive for IgM anti-HAV antibodies and 154 (8.5%) were positive for IgM HEV antibodies. A total of 11 patients (0.60%) were positive for both anti-HAV IgM and anti-HEV IgM antibodies indicating HAV-HEV coinfection. Our study shows that the HAV infection was more prevalent in the pediatric age group. The HEV infection was seen in all age groups and more prevalent in the age group of 20–30 years. The infection was more prevalent from June to October, that is, during monsoon and post-monsoon seasons. Total serum bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), and alkaline phosphatase (ALP) were elevated at 85.84, 86.79, 91.5, and 83.96%, respectively, in HAV-infected and elevated at 78.12, 93.75, 67.18, and 57.03%, respectively, in HEV-infected patients. The patients with HAV-HEV coinfection had all deranged LFTs indicating more severe disease. Conclusion: The present study emphasizes the importance of screening all hepatitis viral markers (A, B, C, E) for early diagnosis and curtailment of outbreaks and epidemics by the public health sector reducing morbidity and mortality.